A Semiotic Analysis of The Ornaments of The Traditional House "Siwaluh Jabu" in The Cultural Village of Lingga, North Sumatra (International Journal of Education and Literature, 2025)
The objective of this investigation is to describe the semiotics of the ornaments found on the traditional Karo house known as Siwaluh Jabu in the cultural village of Lingga. A descriptive-qualitative method was employed in this study. The theoretical framework was based on the semiotic theory of Charles Sanders Peirce. The data were collected through observation, interviews, and documentation. The primary data consist of ornaments located on the exterior parts of the Siwaluh Jabu house. The investigation was conducted in the cultural village of Lingga, located in the Karo Regency, North Sumatra. The findings reveal the presence of various ornaments on the Siwaluh Jabu house, including: (1) buffalo horn, (2) Kudin Taneh, (3) Lumut-Lumut Lawit, (4) Ipen-ipen, (5) Pengret-ret, (6) Pantil Manggis, (7) Bunga Bincole, (8) Pucuk Merbung, (9) Embun Sikawiten, (10) Bindu Matagah, (11) Tapak Raja Sulaiman, (12) Cimba Lau Tutup Dadu, (13) Bindu Matogoh, (14) Teger Tudung, (15) Dapur-dapur, (16) Cuping-cuping, and (17) Taruk-taruk. Each ornament is imbued with symbolic meaning, which is closely connected to the culture, religion, and social structure of the Karo community.